Alternative commercialization pathways for fusion energy systems : proceedings of a workshop. (International Atomic Energy Agency, 2022)
"Fusion energy has potential to contribute to meeting global demand for sustainable energy Increasingly, progressive fusion enterprises are seeking new pathways for the commercialization of the technology, bringing fresh ideas and different perspectives. This publication is a summary of an IAEA Workshop on this topic, outlining the main elements for the development of alternative commercialization pathways for fusion energy systems in the coming decades, bringing together expert opinions from the diverse range of disciplines that are essential to fusion's commercial success. It highlights several critical aspects to consider for new pathways and provides an outline of a roadmap for their development."--Publisher's description.
"June 2022"--Title page verso.
Keywords: Nuclear fusion -- Congresses.; Energy development -- Congresses.; elektronické knihy; electronic books